Li1.2Mn0.6Ni0.2O2 Cathode Material Prepared by the Ultrasonic Dispersion-assisted Method - Fang, Tingting; Chu, Hailiang; Hua, Junqiang; Zhu, Ying; Qiu, Shujun; Bu, Shengzhou; Zhang, Liangbin; Yuan, Mingzhong; Zou, Yongjin; Xiang, Cuili; Zhang, Huanzhi; Yan, Erhu; et al. (Current Mechanics and Advanced Materials (Discontinued), 2021)
Background: Lithium-rich layered materials with high discharge capacity are regarded as one of the most promising cathodes for lithium-ion batteries (LIBs). However, they have been suffering from rapid voltage fading and poor rate performance, which impede their practical application.Methods: Herein, Li1.2Mn0.6Ni0.2O2 with layered structure was successfully prepared by the ultrasonic dispersion-assisted chemical reduction. X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM), transmission electron microscope (TEM) and electrochemical measurements were used to characterize its microstructure and electrochemical properties.Results: The secondary particles of an as-prepared micro/nanostructured sample consist of irregular and sheet-like rectangular blocks. Electrochemical results show that the initial charge and discharge capacity within 2.0 4.8 V is 337.5 mA h g-1 and 236.9 mA h g-1 at 0.2C (1C = 200 mA g-1). The subsequent discharge capacity is stabilized at about 210 mA h g-1 for more than 100 cycles. When the current density is increased to 2C, the cycling columbic efficiency is maintained at 99.3% after 100 cycles.Conclusion: Thus, the Li1.2Mn0.6Ni0.2O2 cathode material prepared by ultrasonic dispersion-assisted chemical reduction has a promising application in LIBs with high energy density and long cycle life.
Keywords: voltage decay